Crafting interactive decoration - Benford, Steve; Koleva, Boriana; Quinn, Anthony; Thorn, Emily-Clare; Glover, Kevin; Preston, William; Hazzard, Adrian; Rennick-Egglestone, Stefan; Greenhalgh, Chris; Mortier, Richard (Association for Computing Machinery, 2017)
We explore the crafting of interactive decoration for everyday artefacts. This involves adorning them with decorative patterns that enhance their beauty while triggering digital interactions when scanned with cameras. These are realised using an existing augmented reality technique that embeds computer readable codes into the topological structures of hand-drawn patterns. We describe a research through design process that engaged artisans to craft a portfolio of interactive artefacts including ceramic bowls, embroidered gift cards, fabric souvenirs and an acoustic guitar. We annotate this portfolio with reflections on the crafting process, revealing how artisans addressed pattern, materials, form and function and digital mappings throughout their craft process. Further reflection on our portfolio reveals how they bridged between human and system perceptions of visual patterns and engaged in a deep embedding of digital interactions into physical materials. Our findings demonstrate the potential for interactive decoration, distil craft knowledge involved in creating aesthetic and functional decoration, highlight the need for transparent computer vision technologies, and raise wider issues for HCI's growing engagement with craft.